Advertising Gay and Lesbian-Themed Films to Mainstream and Niche Audiences: Variations in Portrayal of Intimacy and Stereotypes. Issue 3 (27th May 2017) - Cabosky, Joseph M.
ABSTRACT: Research of gay and lesbian content in advertising materials remains limited. Because most products are not inherently gay or lesbian in nature, this content analysis examined advertisements for gay- and lesbian-themed films from 1980 to 2013. The analysis explored whether there were variations in the portrayal of gay and lesbian content in advertisements depending on the distribution width and date of release. The study therefore explored whether marketing materials differed when films were advertised to mainstream audiences compared to niche audiences. Findings suggested that films marketed to mainstream audiences had advertisements that less frequently portrayed same-sex intimacy. Findings also showed that portrayals of gays and lesbians have generally not changed over time, suggesting that advertisements differ more based on the market segment being reached than the date an advertisement was made. This study fills a gap in the growing area of literature involving gay and lesbian content in advertising.